Internationalizing Higher Education
VIII, 231 p.
Keywords: Globalization is a multifaceted phenomenon, and one of its major components is the internationalization of education. The Increasing pace and complexity of global knowledge flows, and the accelerating exchange of educational ideas, practices and policies, are important drivers of globalization. Higher Education is a key site for these flows and exchanges. This book casts a critical eye on the internationalization of higher education. It peels back taken-for-granted practices and beliefs, explores the gaps and silences in current pedagogy and practices, and addresses the ambiguities, tensions and contradictions in internationalization. In this volume, scholars from a range of disciplines and regions critically examine the co modification of higher education, teaching and support for international students, international partnerships for aid and trade, and the impacts on academics’ work. Peter Ninnes is Coordinator of the Centre for Research on Education in Context at the University of New England, Armidale, Australia. His research interests include comparative and international education, the cultural politics of education, and education in post-conflict societies. He is currently President of the Australian and New Zealand Comparative and International Education Society. Meeri Hellstén is a lecturer in education at Macquarie University, Sydney, Australia. Her research interests are cross-cultural and comparative education, socio-cultural and identity issues in education, e-learning pedagogies, and effective teaching and learning in higher education. She convenes and teaches on a large undergraduate unit in educational psychology.